Faktor-Faktor Yang Mempengaruhi Kinerja Keuangan Dengan Environmental Performnace Sebagai Variabel Intervening - Usman Mustofa; Agung Dharmawan Buchdadi; Umi Widyastuti (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2023)
This study uses a proxy assessment of environmental performance by PROPER-participating firms. The research focuses on an Indonesia Stock Exchange-traded company that will be evaluated as part of the PROPER program between 2019 and 2022. The study found that environmental performance was positively related to return on asset (ROA) and that it was not able to mediate the relationship between the board of commissioners and financial performance. Institutional ownership factors had no effect on environmental performance.